Implementasi Website Sekolah untuk Integrasi Informasi dan Peningkatan Karya Ilmiah MI Muhammadiyah Lubuk Banjar - Putriana, Septi Giseila; Kusuma, Ogy; Mardalena, Ervin; Syafei, Darman (Indo-MathEdu Intellectuals Journal, 2026)
Limited access to school information and low levels of students’ scientific literacy remain major challenges for Islamic elementary schools, particularly in rural areas. MIS Muhammadiyah Lubuk Banjar still relied on conventional media for information dissemination and lacked a structured scientific writing program for students. This community service program aimed to implement a school website as a medium for integrating academic information with the outcomes of paper-writing training for sixth-grade students. The methods employed included website development using the Waterfall model and paper-writing training through a workshop-based approach. The participants consisted of 23 sixth-grade students and 14 teachers of MIS Muhammadiyah Lubuk Banjar. The school website was developed using WordPress with five main pages, while the writing training focused on producing simple and systematic scientific papers. The results indicate that the school website functioned effectively as an information center and a platform for publishing students’ scientific work, and all students successfully produced papers that met the assessment criteria. This program contributes to strengthening school digital literacy and enhancing students’ scientific literacy in support of the sustainable implementation of the Independent Curriculum.